THERE IS NEED OF INTEGRATION OF ULTRASOUND EDUCATION IN UNDERGRADUATE MEDICAL CURRICULUM IN SOUTH ASIA INCLUDING PAKISTAN. - Rano Mal Piryani1,Shomeeta Piryani2,Suneel Piryani3 , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2022)
INTRODUCTION Ultrasound, an imaging technique has widely been used in the management of patients in almost every specialty of medical sciences.1 It is a portable and an inexpensive tool with no hazard of radiation, demonstrate the images in realtime, relatively easy to learn, may be repeated multiple times and helps in urgent decision making. 2 In an attempt to improve the efficiency of patient care and safety, clinicians have started performing ultrasound scans by themselves. 1